ANALISIS PENGUKURAN REDAMAN KABEL SERAT OPTIK ANTARA STO PEMANGKAT â€“ STO TEBAS MENGGUNAKAN OTDR EXFO FTB-200 - ., Indra Lesmana (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
Fiber optic cable as a transmission medium can increase the number of channels, large bandwidth, the ability to send data at high speed, ensure the confidentiality of data sent, not interrupted by the influence of electromagnetic waves on data, voice and video communication system services. The advantages of fiber optic cable communication systems are factors that affect the level of efficiency or performance quality of a fiber optic cable system, such as attenuation, dispersion, power loss, and so on. The attenuation can be caused by internal factors or external factors. Monitoring fiber optic cable transmission network can be measured using the Optical Time Domain Reflectometer (OTDR) EXFO FTB-200 tool so that it can be compared with the results of calculations using the Power Link Budget method to determine the performance of fiber optic cable transmission networks. The results of measurements and calculations on the STO Pemangkat - STO Tebas link are 11 cores within 20.9 Km, attenuation of optical fiber cables is between 2,248 dB - 13,284 dB with breaking points between 5,1145 Km - 14, 7515 Km caused by external factors namely macrobending. The STO Pemangkat - STO Tebas link fiber optic cable transmission network requires repairs or backbone drawdown with a fiber optic cable length between 0.1139 Km - 5.7338 Km. The network is not feasible because the dB/Km attenuation value exceeds the standard of PT. Telkom Telkom so it needs improvement.Â Keywords : Optical Fiber Cable, Attenuation, Bending, Power Link Budget, OTDR EXFO FTB-200.